Impact of Non-Current Assets on the Performance of Firms in Malaysian Construction Sector - Razman, Anuar (Universiti Malaysia Sarawak (UNIMAS), 2021)
Efficient asset management on non-current assets is particularly important for a business because it increases shareholders’ value. For this to happen, management must carefully analyse the options in deciding on the amount of investment needed on non-current assets in its business operations. This research study concerns the effects of non-current assets for construction firms listed in Bursa Malaysia and their relationship with firms’ performance. The efficiency of the firms’ non-current assets is measured by fixed assets turnover, asset tangibility, and total assets turnover mated with return on assets (ROA) and return on equity (ROE), both proxies for firms’ performance. The data collected and analysed in this research focused on the construction sector listed firms under Bursa Malaysia covering the period of 2011 to 2017. The methods employed in this research include descriptive analysis, correlation analysis, and fixed effects model to examine the research objectives. The quality of the data is tested by applying normality, multicollinearity, heteroscedasticity, and auto-correlation tests. The overall results show that the non-current asset turnover in the construction sector has a positive impact on the firms’ performance (ROA and ROE) and significant for this sector. This means that efficiently used non-current asset in the construction sector leads to an increased revenue and improve shareholders wealth. The results of the present study indicate that there is no impact of asset tangibility on both ROA and ROE. It implies that an increase or decrease in levels of asset tangibility does not lead to any changes in firms’ performance. Also, the outcome signifies that total assets turnover does not have an impact on ROA. It means if the construction firms increase in total assets, there will be no changes in ROA. However, total assets turnover has a significantly positive afflation with firms’ performance as measured by ROE. It shows that if the total assets turnover increases, the construction firms are utilising its assets efficiently in the firms’ operational activities resulting increase in revenue and improve firms’ performance. These findings are useful for governments, policymakers, and other stakeholders to develop effective policies, rules, or regulations in promoting economic productivity, growth, and best financing decision.